KECENDERUNGAN BARU PERAN ARSIPARIS KAJIAN DI KANTOR ARSIP UNIVERSITAS INDONESIA: Array - Margareta Aulia Rachman (Arsip Nasional Republik Indonesia, 2018)
This research describes new trends of archivist’s roles in the Archives of University of Indonesia. Technological, social and educational development realm have been influencing these new roles. Collaboration and communication should take place between archivist, librarian and researcher for any different roles as records manager, educator and researcher. Apart from his/ her own expertise in archival principles, archivist should have more skills and specialties in accordance with technological and social development. This research aims to identify the archivist’s roles in an university archives, in this case the Archives of University of Indonesia. This is a qualitative research. The data is collected by observing, interview and literature studies. The informants are choosen by applying purpossive sampling method that include among others the chairwoman and the qualified archivists of the archives. The result shows that the evolving roles of the archivist could develop the archives’ achievement in turn. These new roles are including digital archivist, researcher and educator. Apart from those, archivist should maintain his/ her roles as past guardian and librarian-archivist.